Denoising of Satellite Images Using Hybrid Filtering and Convolutional Neural Network - Mohan, E; Sivakumar, R. (International Journal of Engineering and Technology, 2018)
The concept of machine learning is useful for various applications and the Convolutional Neural Network (CNN) plays a major role on it. This paper proposes the denoising of satellite images using the machine vision. The noise in an image cannot be find out without distinguish the information and noise. The CNN differentiates the actual information and it is separated by the noise and applying the method to remove the noise. Also, it balances the effect of removing the noise from the original image. The noise removal image is enhanced for better visualization and the quality of the enhanced image is measured with Mean Square Error (MSE) and Peak Signal to Noise Ratio (PSNR)Â Â